2002
DOI: 10.1016/s1074-7613(02)00274-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intestinal Inflammatory Condition Generates IL-10-Producing Regulatory B Cell Subset Characterized by CD1d Upregulation

Abstract: B cells possess a variety of immune functions that are involved in normal and abnormal immune responses, including autoimmune disorders. Through murine models of intestinal inflammation, we here demonstrate a B cell subset that is induced in gut-associated lymphoid tissues and is characterized by CD1d upregulation. This B cell subset appears under a chronic inflammatory environment, produces IL-10, and suppresses progression of intestinal inflammation by downregulating inflammatory cascades associated with IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
765
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 861 publications
(798 citation statements)
references
References 59 publications
23
765
0
10
Order By: Relevance
“…B-1 B cells appear to suppress colitis since their absence in the Gαi2 knockout mice makes them susceptible to inflammatory bowel disease (61). Control of colitis by B cells has been proposed to be due to IL-10 secretion from B-1 cells (62). Our preliminary studies show that B-1 cell production of IL-10 is not increased in the absence of CD5 (Sindhava et al unpublished results).…”
Section: Discussionmentioning
confidence: 70%
“…B-1 B cells appear to suppress colitis since their absence in the Gαi2 knockout mice makes them susceptible to inflammatory bowel disease (61). Control of colitis by B cells has been proposed to be due to IL-10 secretion from B-1 cells (62). Our preliminary studies show that B-1 cell production of IL-10 is not increased in the absence of CD5 (Sindhava et al unpublished results).…”
Section: Discussionmentioning
confidence: 70%
“…After depletion of mucosal B cells by anti-CD20 (Rituximab) in a patient with ulcerative colitis, local IL-10 production was abolished, resulting in an acute clinical exacerbation [47]. The regulatory, IL-10-mediated potential of B lymphocytes, has also been shown in vivo to be essential to limit immunopathology in murine models of autoimmune diseases, such as EAE [48], and inflammatory bowel disease [49]. In patients with systemic lupus erythematosus, vitamin D deficiency was correlated to the presence of anti-nuclear antibodies and disease activity, and has been discussed as important factor in the regulation of B cell functions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that B cells and their autoantibody products suppress colitis in T cell receptor alpha chain-deficient mice that spontaneously develop chronic colitis, while B cells are not required for disease initiation [78]. B cells with upregulated CD1d expression in the gut-associated lymphoid tissues of mice with intestinal inflammation were subsequently demonstrated to be regulatory [25]. This IL-10-producing B cell subset appears during chronic inflammation in T cell receptor alpha chain-deficient mice and suppresses the progression of intestinal inflammation by downregulating inflammatory cascades associated with IL-1 upregulation and signal transducer and activator of transcription 3 ( stat3 ) activation rather than by altering polarized T H cell responses.…”
Section: B10 Cells In Mouse Models Of Autoimmune Diseasementioning
confidence: 99%